Modifications of real code genetic algorithm for global optimization - Tsoulos, Ioannis G. (Applied mathematics and computation, 2008)
A series of modifications to the real coded genetic algorithm for the task of locating the global minimum of multidimensional functions are presented here. These modifications include a new stopping rule, a novel mutation mechanism and a periodically application of a local search procedure. The proposed modifications are tested on a series of optimization problems and the results are reported.